2019
DOI: 10.1038/s41467-018-07923-2
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor STAT5 catalyzes Mannich ligation reactions yielding inhibitors of leukemic cell proliferation

Abstract: Protein-templated fragment ligations have been established as a powerful method for the assembly and detection of optimized protein ligands. Initially developed for reversible ligations, the method has been expanded to irreversible reactions enabling the formation of super-additive fragment combinations. Here, protein-induced Mannich ligations are discovered as a biocatalytic reaction furnishing inhibitors of the transcription factor STAT5. STAT5 protein catalyzes multicomponent reactions of a phosphate mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 48 publications
0
50
1
2
Order By: Relevance
“…Although tetrazoles were not active against STAT5B (>10 mM), the ligation products showed substantial activity, which the authors attribute to super-additive binding interactions. Intracellular physiological concentrations of formaldehyde also emphasize the viability of this molecule as a STAT inhibitor and the utility of bio-catalytic Mannich reactions [105]. A study by Juen et al reported the optimization of the STAT5 inhibitor, Cpd17f (Figure 3v) [103].…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…Although tetrazoles were not active against STAT5B (>10 mM), the ligation products showed substantial activity, which the authors attribute to super-additive binding interactions. Intracellular physiological concentrations of formaldehyde also emphasize the viability of this molecule as a STAT inhibitor and the utility of bio-catalytic Mannich reactions [105]. A study by Juen et al reported the optimization of the STAT5 inhibitor, Cpd17f (Figure 3v) [103].…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…36 Recently Rademann and co-workers demonstrated that α-ketophosphonates, and particularly 4-phosphonocarbonyl phenylalanine (pcF), can also be used as photoactive enzymatically stable phosphotyrosine mimetics targeting, deactivating and labelling phosphotyrosine binding proteins. [81][82][83] For example, pcF was incorporated into the sequence of a STAT5 SH2 domaindirected peptide, labelled with 5,6-carboxyfluorescein (CF) for binding studies and protein detection. 81 The resulting peptide 5-CFGpcFLSLPPW-NH 2 exhibited 20-fold reduced binding affinity in comparison to a native phosphotyrosinecontaining peptide.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…This approach was utilised to pull-down STAT5 from cell lysates using a similar pcF-containing, but dual-labelled (carboxyfluorescein and biotin) STAT5-SH2binding peptide, and was applied to confirm selectivity of the studied inhibitors. 82 To integrate pcF into peptides, Horatscheck et al developed building block 10 for Fmoc SPPS (Fig. 9B).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…
Fragment-based drug discovery has been established as a powerful method for the assembly of optimized protein ligands. We employed protein-templated ligations, initially for the site-directed detection of low-affinity fragments and subsequently for the identification of potent fragment combinations that are useful as chemical tools [1][2][3][4].Reversible and irreversible reactions have been employed for ligand construction. Here, we will reflect on the reaction scope of protein-catalyzed ligand formation and consider the thermodynamic and kinetic implications of the reactions.
…”
mentioning
confidence: 99%
“…Fragment-based drug discovery has been established as a powerful method for the assembly of optimized protein ligands. We employed protein-templated ligations, initially for the site-directed detection of low-affinity fragments and subsequently for the identification of potent fragment combinations that are useful as chemical tools [1][2][3][4].…”
mentioning
confidence: 99%